Obtenção e caracterização molecular e fisiológica de plantas de soja contendo o gene AtGolS2 sob déficit hídrico - Honna, Patrícia Teruko [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
With the current scenario of climate change, there is a tendency to longer and recurrent drought events, thus obtaining more drought tolerant plants figure as a major investment in the national science and technology. Raffinose family oligosaccharides (RFOs) plays multiple functions in plants and it is known that these are accumulated in plant tissues in water deficit situations, guaranteeing the stability of cell membranes, thus maintaining the vital functions of the plant. In turn, galactinol synthase (GolS, EC 2.4.1.123) catalyzes the first step in the biosynthesis of RFOs plays an important regulatory role in carbon partitioning between sucrose and orphans. Thus, our objective was to introduce gene construction 35S:AtGolS2 via Agrobacterium tumefaciens in soybean plants and characterize molecularly and physiologically events obtained under water deficit. In this context, the conventional soybean BRS 184 was used in the transformation process and the soybean events were molecularly characterized in regard to the transgene copy number by qPCR technique. For the analysis of constitutive gene expression total RNA of events, well-watered conditions, was extracted and the expression determined by RT-qPCR. The segregation rate was calculated using the X2 test (p ≤ 0.05). Based on our results, two events (2Ia1 and 2Ia4) were selected to be analyzed for physiological responses under drought simulated under greenhouse conditions. The results showed that the plants 2Ia4 event the largest accumulation of water associated with lower leaf area in the control condition led to maintenance of gas exchange caused by the reduction in leaf transpiration, increased water accumulation in the substrate and accumulation of raffinose and galactinol transcripts in tissues. Thus, the increased levels of these carbohydrates would have made these act as osmoprotectors, enabling the recommendation of 2Ia4 plants breeding programs aimed at tolerance to drought

Com o atual cenário de mudanças climáticas, observa-se a tendência a eventos de seca mais longos e recorrentes, desta forma a obtenção de plantas mais tolerantes à seca figura como um dos principais investimentos dentro da ciência e tecnologia nacional. Os oligossacarídeos da família das rafinoses (RFOs) desempenham múltiplas funções nas plantas e sabe-se que estes são acumulados nos tecidos vegetais em situações de déficit hídrico, garantindo a estabilidade das membranas celulares, consequentemente mantendo as funções vitais da planta. Por sua vez, a enzima galactinol sintase (GolS, EC 2.4.1.123), catalisa o primeiro passo na biossíntese dos oligossacarídeos dos RFOs desempenhando um importante papel regulador na partição do carbono entre sacarose e RFOs. Desta forma, o objetivo do presente trabalho foi introduzir em soja, via Agrobacterium tumefaciens, a construção gênica 35S:AtGolS2 e caracterizar molecularmente e fisiologicamente os eventos obtidos sob déficit hídrico. Para o processo de transformação, a cultivar convencional de soja BRS 184 foi utilizada e os eventos obtidos foram caracterizados quanto ao número de cópias através da técnica de qPCR. Para a análise da expressão gênica constitutiva o RNA total dos eventos, em condições bem irrigadas, foi extraído e a expressão determinada via RT-qPCR. A taxa de segregação foi calculada através do teste do X2 (p≤ 0.05). Com base nos resultados obtidos, dois eventos (2Ia1 e 2Ia4) foram selecionados para serem analisados quanto a respostas moleculares e fisiológicas sob déficit hídrico induzido em condições de casa de vegetação. Os resultados mostraram que nas plantas do evento 2Ia4 o maior acumulo de água associado a menor área foliar na condição controle levou a manutenção das trocas gasosas causado pela redução na transpiração foliar, maior acúmulo de água no substrato e acúmulo de transcritos de rafinose e galactinol nos tecidos
Keywords: Soja; Oligossacarideos; Enzimas; Plantas - Resistencia a seca; Genetica vegetal; Oligosaccharides